Pengaruh Digital Marketing, Word Of Mouth Dan Product Quality Terhadap Brand Awareness Produk Distro (Studi Pada Pelanggan Produk Distro Davi Mbois Store Malang) - Yoherga, Galang; Slamet, Afi Rachmat; Millaningtyas, Restu (UNIVERSITAS ISLAM MALANG, 2024)
Abstract Social media functions as a medium for communication and socialization but can also be utilized for various purposes. This study aims to analyze the impact of digital marketing, word of mouth, and product quality on brand awareness of the Davi Mbois Store Malang's products. The sampling technique used was random sampling with a Likert scale, resulting in 100 respondents. Data collection was carried out through surveys using questionnaires.The results show that digital marketing, word of mouth, and product quality simultaneously (F) significantly impact brand awareness. Partially, the variables of digital marketing (X1) and product quality (X3) have a significant effect on brand awareness (Y), while word of mouth (X2) does not have a significant partial effect (t). The simultaneous test results indicate that variations or changes in brand awareness can be explained by digital marketing, word of mouth, and product quality. The partial test results show that digital marketing and product quality significantly affect brand awareness, while word of mouth does not significantly affect brand awareness. Keywords: Digital Marketing, Word of Mouth, Product Quality and Brand Awareness